Immunoglobulin A nephropathy in a patient with neurofibromatosis type 1: A case report and literature review. Issue 42 (22nd October 2021) - Rhee, Harin; Kim, Sungmi; Lee, Wanhee; Jeon, Hakeong; Kim, Da Woon; Ye, Byung-Min; Kim, Hyo Jin; Kim, Min Jeong; Kim, Seo Rin; Kim, Il Young; Song, Sang Heon; Seong, Eun Young; et al.
Abstract: Rationale: Neurofibromatosis type 1 (NF-1) is an autosomal-dominant neurocutaneous disorder that affects the skin, bones, and nervous system. The most common manifestation of kidney involvement is renal artery stenosis; glomerulonephritis is extremely rare. In this case report, we present a patient with NF-1 and immunoglobulin A nephropathy (IgAN). Patient concerns: A 51-year-old Korean man previously diagnosed with NF-1 presented with persistent proteinuria and hematuria identified during a routine medical check-up. He had no history of hypertension or diabetes, and denied a history of alcohol use or smoking. Diagnosis: The contrast-enhanced computed tomography scan revealed normal-sized kidneys and no evidence of renal artery stenosis. On the day of the kidney biopsy, laboratory tests showed a serum creatinine level of 1.1 mg/dL, urine protein/creatinine ratio of 1.3 g/g, and urine red blood cell count of >10 to 15/HPF. The kidney biopsy sample revealed IgAN grade III, according to Lee glomerular grading system. Intervention: The patient was advised to take 4 mg of perindopril. Outcome: Three months after the treatment, the urine protein/creatinine ratio decreased to 0.6 g/g, with no change in the serum creatinine level (1.03 mg/dL). Lessons: A genetic link between NF-1 and IgAN or other glomerular diseases is not established. However, activation of the mTOR pathway may explain this association.